Unexplained Infertility and Ayurveda - A Case Study - Deepika Bhadre; Mangesh Mundhe; Reshma Halambre (AYUSHDHARA, 2025)
Case of infertility in which cause remains unknown or idiopathic is considered as an unexplained infertility. Literally the couple who fails to conceive within one year of unprotected coitus with normal investigations of both the partners is termed as Unexplained infertility. Globally about 10-30% of infertility cases are diagnosed as unexplained infertility. Day by day the prevalence rate is rising due to change in lifestyle, unhealthy food habits, drinking alcohol & smoking addiction and stress. In Ayurveda Acharyas have given detailed description of infertility and it’s line of treatment with many formulations. In present scenario a case of 30 years female was undertaken who had visited our OPD of DAMCH, Udgir with complaints of anxious to conceive and trying for that from last 3 years. The couple was examined and investigated after which diagnosed as unexplained infertility because all the investigations were absolutely normal. As Acharyas have given line of treatment for infertility we gave her Shodhan chikitsa first followed by Shaman and Garbhasthapak chikitsa, as a result we got positive pregnancy test indicating conception within 6 months with healthy pregnancy.